2011
DOI: 10.1007/s00056-010-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on orthodontic space closure after guided bone regeneration

Abstract: Orthodontic tooth movement using this bone replacement material is possible according to these study results. This technique, thus, warrants further investigation in future clinical trials focusing on preventive means to reduce the development of gingival invaginations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 17 publications
1
29
0
9
Order By: Relevance
“…Cardaropoli et al have shown the resorption capacity of this material after 14 days have passed 13 . These findings are still debatable and there seems to be agreement that the longer the movement is delayed, the lesser the risk 44 .…”
Section: ò1mentioning
confidence: 97%
See 1 more Smart Citation
“…Cardaropoli et al have shown the resorption capacity of this material after 14 days have passed 13 . These findings are still debatable and there seems to be agreement that the longer the movement is delayed, the lesser the risk 44 .…”
Section: ò1mentioning
confidence: 97%
“…The authors emphatically insist on the need to adapt the therapy to the speed of resorption of the material and to its properties for remodeling, for angio-genesis, osteo-induction and osteo-conduction 44 . Cardaropoli et al have shown the resorption capacity of this material after 14 days have passed 13 .…”
Section: ò1mentioning
confidence: 99%
“…Gingival invaginations display hyperplastic changes including epithelial hyper keratinization with pronounced depth proliferation at the edges of the invagination. [7][8][9] Stimulation from the orthodontic forces has been reported to be responsible for the hyperplastic tissue reaction. 10 Malkoc et al 11 attributed these histological changes to the interruption of the continuity of the gingival fiber system and bone remodeling that occur with destruction of the cortical plates, socket healing, and root movement.…”
Section: 5005/jp-journals-10024-2001mentioning
confidence: 99%
“…Allerdings liegen hierzu bislang nur präliminäre Daten vor; beispielsweise führten Reichert et al [17] eine Pilotstudie an 3 Patienten im Split-Mouth-Design durch. Das Auffüllen der Prämolarenextraktionsal-veolen erfolgte einseitig mit resorbierbarem Knochenersatzmaterial sowie einem Gewebekleber zur Abdeckung.…”
Section: Therapieunclassified